DAMPAK KERENTANAN PERUBAHAN IKLIM TERHADAP KEBERLANJUTAN KETAHANAN PANGAN - Fadilla, Meita Indah; Pamungkas, Tegar Adi (Media Ekonomi, 2024)
Climate change vulnerability is the phenomenon of the extent to which a system of both humans and the natural environment is vulnerable or has the potential to experience negative impacts due to climate change. This research tries to see how food security is affected by climate change vulnerability and the aspects that develop in it. Multiple linear regression using the Ordinary Least Square (OLS) model and cross-sectional data for 2023 in 38 districts and cities in East Java with composite index calculation is the research approach used to estimate the climate change vulnerability index and its forming dimensions. Food security is significantly impacted by climate change vulnerability, according to the findings, with the adaptive capacity dimension having a positive influence and the ecological and human sensitivity dimensions having negative consequences.  Nearly one-third of the total effect was attributed to the strong influence of adaptive capacity.  This study indicates that susceptibility to climate change presents a significant risk to regional stability, which needs to be addressed and avoided by cooperation between local communities, the corporate sector, and government agencies.  The implementation of sustainable farming methods, the shift to renewable energy, and the development of adaptive capability are all necessary to guarantee the supply of high-quality resources.